Composite loudspeaker diaphragm for car audio and preparation method thereof
Patent Information
- Application Number
- CN202611145044.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]为了解决现有复合振膜其层间界面缺乏对温度-湿度循环载荷的有效抵抗能力的问题,本申请提供一种汽车音响用的复合喇叭振膜及其制备方法
1、通过玄武岩表面毡层、麻纤维毡层和玄武岩表面毡层的三明治结构,实现了高刚度与高内阻尼的平衡。外层玄武岩纤维的协同增强作用提升了振膜刚度,有效抑制低频分割振动及车厢声场耦合。芯层麻纤维利用其天然中空结构及氢键网络提供优异内阻尼,快速耗散振铃能量,从而缩短衰减时间,改善瞬态响应,解决人声发闷及定位涣散等问题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of speaker diaphragm technology, and more specifically, to a composite speaker diaphragm for automotive audio and its preparation method. Background Technology
[0002] With the upgrading of automobile consumption and the rapid development of in-car entertainment systems, car audio has become one of the important indicators for measuring the driving experience. In practical applications, the interior of a car cabin is not an ideal free sound field environment. Hard reflective surfaces such as the windshield, side windows, and dashboard are interspersed with soft sound-absorbing materials such as fabric seats, headliners, and carpets, creating a large number of early reflections and reverberation superpositions. Actual measurements show that the sound field non-uniformity of a typical family car cabin in the 200Hz-500Hz frequency band can reach ±6dB or more. This special acoustic environment with strong reflections and high sound pressure level fluctuations places much higher demands on the design of speaker diaphragms than ordinary indoor audio systems.
[0003] Within the aforementioned frequency band, if the frequency of the diaphragm's split vibration due to insufficient rigidity falls within this band, it will couple and amplify with the acoustic characteristics of the car cabin, creating a harsh booming or coloration effect. Simultaneously, if the diaphragm damping is insufficient and the ringing decay time is too long, the transient signal, already affected by the car cabin reverberation, will become further blurred, resulting in sluggish drum beats, muffled vocals, and scattered instrument positioning, severely impacting the listening experience. Therefore, car audio diaphragms must simultaneously possess high specific stiffness to suppress split vibrations and appropriate internal damping to quickly dissipate ringing energy; both are indispensable.
[0004] To meet the aforementioned performance requirements, existing automotive audio speaker diaphragms typically employ a multi-layered composite structure composed of carbon fiber, Kevlar, glass fiber, or metal layers and a resin matrix. This type of composite diaphragm utilizes the synergistic effect between the various material layers to achieve a certain degree of high specific stiffness and appropriate internal damping, thereby ensuring the diaphragm's dimensional stability and acoustic consistency.
[0005] However, the actual service environment of automotive audio diaphragms is extremely harsh. When a car is parked outdoors, the interior temperature can reach over 70°C under the summer sun, and drop below -30°C in frigid winter regions. Meanwhile, the rainy season in southern China and the use of air conditioning cause the relative humidity inside the car to fluctuate frequently between 30% and 90%. The coefficients of thermal expansion and hygroscopic expansion rates of the resin matrix and the reinforcing fibers (carbon fiber, glass fiber, etc.) or metal layers differ significantly. Under repeated temperature-humidity cyclic loading, incompatible deformation occurs between the layers. Existing composite diaphragms primarily rely on physical anchoring and van der Waals forces for interlayer bonding, resulting in limited interfacial shear strength, which is insufficient to effectively resist the aforementioned incompatible deformation, thus inducing cracks or interlayer debonding. After interface deterioration, the load transfer efficiency between layers decreases, the overall stiffness of the diaphragm decreases, and the split vibration frequency shifts to lower frequencies, making it more susceptible to falling within the sensitive range of cabin sound field fluctuations.
[0006] In summary, while existing composite diaphragms can achieve a balance between high specific stiffness and appropriate internal damping in their initial state, their interlayer interfaces lack effective resistance to temperature-humidity cyclic loads. This results in a significant decrease in acoustic performance over time, making it impossible to maintain high-fidelity sound quality in the harsh acoustic environment of a car cabin for extended periods. Therefore, there is an urgent need for a car audio speaker diaphragm with excellent interlayer interface durability to simultaneously meet the dual requirements of high-fidelity acoustic performance and long-term environmental stability. Summary of the Invention
[0007] To address the problem that existing composite diaphragms lack effective resistance to temperature-humidity cyclic loads at their interlayer interfaces, this application provides a composite speaker diaphragm for automotive audio systems and its preparation method.
[0008] In a first aspect, this application provides a composite speaker diaphragm for automotive audio systems, employing the following technical solution: A composite speaker diaphragm for car audio systems comprises, in sequence, a first basalt surface felt layer, a hemp fiber felt layer, and a second basalt surface felt layer. Both the first and second basalt surface felt layers are prepared from the following raw materials in parts by weight: 60-80 parts of basalt fiber 5-10 parts polyester fiber 3-5 parts of aramid fiber Appropriate amount of phenolic resin glue The basalt fiber is obtained by mixing three types of basalt fibers of different lengths and diameters.
[0009] The hemp fiber felt layer is prepared from the following raw materials in parts by weight: 80-90 parts of hemp fiber 4-6 parts nylon fiber Appropriate amount of phenolic resin adhesive.
[0010] By adopting the above technical solution, a sandwich structure consisting of a first basalt surface felt layer, a hemp fiber felt layer, and a second basalt surface felt layer is used. The synergistic reinforcement effect of basalt fibers of different lengths and diameters in the basalt surface felt layer, along with polyester and aramid fibers, significantly improves the stiffness of the diaphragm, effectively suppresses low-frequency segmented vibration, and reduces its coupling with the sensitive frequency band of 200Hz-500Hz in the non-uniform sound field of the carriage. Specifically, mixing the three types of basalt fibers of different lengths and diameters in a specific ratio creates a gradient porous structure within the felt layer, consisting of a coarse fiber skeleton, a medium fiber filling transition, and a fine fiber dense surface layer. This structure not only increases the specific surface area, allowing phenolic resin adhesive to fully penetrate and form a three-dimensional network of bonding nodes at fiber intersections, further enhancing the cohesive strength of the felt layer itself and the interfacial mechanical interlocking with adjacent hemp fiber felt layers, but also allows the micro-stress generated by fibers of different scales under temperature and humidity changes to be gradually dispersed through the gradient structure, avoiding interfacial cracking caused by concentrated stress on fibers of a single scale. The combination of the high toughness of aramid fiber and the good interfacial affinity of polyester fiber further improves the impact resistance and resin impregnation uniformity of the surface felt layer, enabling the surface felt layer to maintain dimensional stability under drastic temperature changes from -30℃ to 70℃, and preventing interlaminar shear failure induced by thermal expansion and contraction.
[0011] Meanwhile, the excellent internal damping characteristics brought about by the natural hollow structure of hemp fibers and the rich hydrogen bond network between cellulose molecular chains enable the diaphragm to quickly dissipate ringing energy during vibration, shorten the ringing decay time, improve transient response performance, and avoid problems such as sluggish drumbeats, muffled vocals, and scattered instrument positioning. This allows the diaphragm to simultaneously meet the dual acoustic requirements of high specific stiffness and appropriate internal damping in its initial state. The entangled complementary structure formed by nylon fibers and hemp fibers improves the flexibility of the hemp fiber felt layer and its wettability with phenolic resin, enabling the phenolic resin adhesive to form a continuous and dense adhesive layer at the three-layer interface during the hot pressing process of the sandwich structure. The first basalt surface felt layer, the hemp fiber felt layer, and the second basalt surface felt layer are bonded together by phenolic resin adhesive to form a strong bonding interface. This allows the three-layer structure to withstand temperature cycles of -30℃ to 70℃ and relative humidity cycles of 30% to 90%, suppressing the uncoordinated deformation between the layers and maintaining the interlayer shear strength over a long period. This effectively avoids the initiation of interface cracks and interlayer debonding caused by differences in thermal expansion and contraction and hygroscopic expansion.
[0012] Preferably, the basalt fiber is composed of basalt fibers with a length of 1-10 mm and a diameter of 1-5 μm, basalt fibers with a length of 15-40 mm and a diameter of 10-30 μm, and basalt fibers with a length of 50-80 mm and a diameter of 9-15 μm in a weight ratio of 10:4-7:1-3.
[0013] By adopting the above technical solution, three different specifications of basalt fibers were graded in a weight ratio of 10:4-7:1-3, which optimized the fiber network structure. Short fine fibers filled the pores formed by the interweaving of long coarse and medium-length fibers, further improving the density and uniformity of the felt layer. Long coarse fibers provided the main load-bearing skeleton to ensure high specific stiffness, medium-length fibers played a bridging role, and short fine fibers enhanced the interfacial bonding and stress transfer efficiency. The three worked together to make the penetration and anchoring of phenolic resin more complete, significantly improving the interlaminar shear strength and interfacial durability, effectively resisting the uncoordinated deformation under temperature-humidity cyclic loading, inhibiting interlaminar debonding and crack initiation, and ensuring that the diaphragm maintains high-fidelity acoustic performance in the harsh car environment for a long time.
[0014] Preferably, the polyester fiber has a length of 30-50 mm and a fineness of 1.5-3D; The aramid fibers are 10-20 mm in length and 1.5-2D in fineness.
[0015] By adopting the above technical solution, polyester fibers of specific specifications are blended with aramid fibers. The polyester fibers, with their appropriate length and fineness, fill the gaps in the basalt fiber skeleton, enhancing the flexibility and resin wettability of the felt layer. The aramid fibers, with their high strength, high modulus, and excellent affinity with phenolic resin, form bridging anchors at fiber intersections, significantly improving the interlayer shear strength and fatigue resistance, and effectively suppressing interlayer debonding under temperature and humidity cycling.
[0016] Preferably, the basalt fibers are pretreated by the following method: Basalt fibers were immersed in a silane coupling agent ethanol solution for 20-30 minutes, then removed and dried to obtain pretreated basalt fibers.
[0017] By adopting the above technical solution, organic functional groups are introduced into the surface of basalt fiber, which greatly improves the interfacial compatibility between basalt fiber and phenolic resin adhesive, thereby significantly improving the interfacial bonding strength and resistance to humid heat aging, and effectively inhibiting interfacial deterioration and interfacial debonding under temperature and humidity cycling.
[0018] Preferably, the length of the hemp fiber is 20-50 mm, and the metric count is 10-20 Nm; The nylon fibers are 10-25mm in diameter and have a fineness of 1.5-6D.
[0019] By adopting the above technical solutions and optimizing the length and metric count of hemp fibers, the cohesion and structural integrity of the felt layer are ensured. The higher count results in finer fibers, increasing the specific surface area and facilitating the full impregnation of phenolic resin, thereby improving internal damping performance. Combined with specific nylon fibers, their elastic bridging effect improves the flexibility and resilience of the hemp fiber felt layer, enhances the interfacial adhesion with the basalt surface felt layer, effectively buffers interlayer stress under temperature and humidity cycles, and inhibits interfacial debonding.
[0020] Preferably, the phenolic resin adhesive is composed of phenolic resin, a softener, a penetrant, and a solvent in a weight ratio of 70-80:4-8:0.1-0.3:70-80.
[0021] By employing the above technical solutions, the phenolic resin forms a dense cross-linked network after curing, endowing the adhesive layer with excellent high-temperature resistance, damp-heat resistance, and creep resistance, ensuring the long-term stability of the interlayer interface under high temperature and humidity cycling conditions from -30℃ to 70℃. The flexibility agent effectively improves the brittleness of the phenolic resin, enhances the toughness and impact resistance of the adhesive layer, and buffers the interlayer stress caused by the mismatch between fiber and resin due to thermal expansion and hygroscopic expansion. The penetrant reduces the surface tension of the adhesive, promoting deep penetration and uniform coating of the phenolic resin into the basalt fiber felt layer and hemp fiber felt layer, strengthening the fiber-resin interface adhesion. The solvent adjusts the viscosity of the adhesive, ensuring uniform impregnation. The synergistic effect of these four agents significantly improves the interlayer interface shear strength and durability, effectively inhibiting interlayer debonding and crack initiation caused by temperature and humidity cycling.
[0022] Preferably, the thickness ratio of the first basalt surface felt layer, the hemp fiber felt layer, and the second basalt surface felt layer is 0.5-1:5:0.5-1.
[0023] By adopting the above technical solution, a high-damping hemp fiber felt layer is used as the main core layer, and thin basalt surface felt layers on both sides provide rigid constraints, forming a highly efficient sandwich structure. The high specific stiffness of the outer layer effectively suppresses segmented vibrations, the large proportion of the core layer thickness ensures sufficient internal damping, and the thin outer layer reduces the overall mass, thus balancing acoustic performance and lightweight requirements.
[0024] Secondly, this application provides a method for preparing a composite speaker diaphragm for automotive audio systems, employing the following technical solution: A method for preparing a composite speaker diaphragm for automotive audio systems includes the following preparation steps: Preparation of basalt surface felt layer: Basalt fiber, polyester fiber and aramid fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out and cured to obtain basalt surface felt layer. Preparation of hemp fiber felt layer: Hemp fiber and nylon fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out, cured, and hemp fiber felt layer is obtained. Preparation of composite speaker diaphragm: The wuyan surface felt layer, the hemp fiber felt layer and the wuyan surface felt layer are stacked in sequence, placed in a molding equipment, and pressed to form a composite speaker diaphragm for car audio.
[0025] Preferably, the needle-punching process in the preparation of the felt layer on the Wuyan surface is as follows: The procedure involves alternating between the front and back sides of the needle. First, pre-needling is performed with a needle density of 150-250 needles / cm², a needle depth of 8-12mm, and a feed speed of 2-4m / min. Then, the main needle is performed with a needle density of 400-800 needles / cm², a needle depth of 10-14mm, and a feed speed of 4-6m / min.
[0026] Preferably, the needle-punching process in the preparation of the hemp fiber felt layer is as follows: The procedure involves alternating between the front and back sides of the needle. First, pre-needling is performed with a needle density of 250-350 needles / cm², a needle depth of 6-10mm, and a feed speed of 1-2m / min. Then, the main needle is performed with a needle density of 700-900 needles / cm², a needle depth of 12-15mm, and a feed speed of 3-5m / min.
[0027] By employing the above-mentioned technical solution, this preparation method uses dry carding and needle punching processes to prepare basalt surface felt layers and hemp fiber felt layers, respectively. This allows the fibers in each layer to form a three-dimensional entangled network structure, improving the cohesion and structural uniformity of the felt layers. The needle punching process induces longitudinal fiber migration, enhancing the mechanical interlocking between fibers within the layer and providing abundant anchoring sites for subsequent impregnation and curing of phenolic resin adhesive. After impregnation and curing, the resin fully coats the fibers and fills the pores, forming a dense and high-strength fiber-reinforced composite material layer. Finally, the three layers of felt are stacked sequentially and pressurized. Under pressure, the phenolic resin undergoes a certain degree of interlayer flow and fusion, forming a continuous resin bonding interface between the basalt surface felt layer and the hemp fiber felt layer, eliminating the weak interfacial zones that may exist in traditional physical lamination. The composite speaker diaphragm prepared by this process has an outer basalt surface felt layer with high specific stiffness to suppress split vibration, and a core hemp fiber felt layer to provide excellent internal damping to quickly dissipate ringing energy. At the same time, the layers are strongly bonded through resin fusion and fiber entanglement, which effectively resists interlayer incoordination deformation under temperature-humidity cycles, ensuring that the diaphragm maintains high-fidelity sound quality and structural integrity in the harsh car cabin environment for a long time.
[0028] Preferably, the temperature of the upper and lower molds in the molding equipment is 210-230℃, the molding pressure is 0.2-0.4MPa, the hot mold molding time is 20-30S, and the cold mold setting time is 5-10S.
[0029] By employing the above technical solution, appropriate temperature allows the phenolic resin to fully melt and flow, undergoing deep cross-linking and curing to form a dense and high-strength chemical bonding interface between the layers. Appropriate molding pressure ensures tight adhesion of the three-layer felt, promoting mutual penetration and fusion of the resin at the interface and effectively eliminating air bubbles and weak bonding areas. Hot molding time guarantees the degree of resin curing, while cold molding allows the diaphragm to cool and solidify rapidly, preventing warping and deformation after demolding. The synergistic effect of these processes improves the interlayer shear strength, dimensional stability, and temperature and humidity cycling durability of the diaphragm.
[0030] In summary, this application has the following beneficial effects: 1. A sandwich structure consisting of a basalt surface felt layer, a hemp fiber felt layer, and another basalt surface felt layer achieves a balance between high stiffness and high internal damping. The synergistic reinforcement of the outer basalt fiber layer enhances the diaphragm stiffness, effectively suppressing low-frequency split vibrations and cabin sound field coupling. The core hemp fiber layer utilizes its natural hollow structure and hydrogen bond network to provide excellent internal damping, rapidly dissipating ringing energy, thereby shortening the decay time, improving transient response, and solving problems such as muffled vocals and unclear positioning.
[0031] 2. The gradient pore structure formed by three different sizes of basalt fibers increases the specific surface area and forms a three-dimensional network of bonding nodes. Combined with the high toughness of aramid fibers and the interfacial affinity of polyester fibers, it not only improves the cohesive strength of the felt layer itself, but also enhances the interlayer mechanical interlocking, so that the diaphragm has excellent impact resistance while maintaining dimensional stability.
[0032] 3. Through fiber synergistic reinforcement and resin impregnation optimization, the three-layer structure can effectively suppress the uncoordinated deformation between layers under drastic temperature changes from -30℃ to 70℃ and humidity cycles of 30%-90%, ensuring the long-term maintenance of interlayer shear strength and preventing interface cracks and interlayer debonding caused by differences in thermal expansion and contraction or moisture absorption expansion. Detailed Implementation Example
[0033] The basalt fiber is sourced from Zhejiang Shijin Basalt Fiber Co., Ltd., and the length and diameter are customized as needed.
[0034] The polyester fiber is selected from polyester staple fiber from Zhejiang Anshun Chemical Fiber Co., Ltd., with models of 1.5D, 2D, and 3D, and the length can be customized as needed.
[0035] The aramid fibers are selected from aramid fibers from Yantai Taihe New Materials Co., Ltd., with finenesses of 1.5D, 1.8D, and 2D, and lengths can be customized as needed.
[0036] The flax fiber is selected from Zhejiang Jinyuan Flax Co., Ltd., with metric counts of 10Nm, 15Nm, and 20Nm, and the length can be customized as needed.
[0037] The nylon fiber is selected from Nylon 6 from Shangyu Jiusheng Chemical Fiber Co., Ltd., with fineness of 1.5D, 4D and 6D respectively, and the length can be customized according to the needs.
[0038] Example 1
[0039] A composite speaker diaphragm for automotive audio is prepared by the following method: Preparation of basalt surface felt layer: Basalt fiber, polyester fiber and aramid fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out and cured to obtain basalt surface felt layer. The basalt fiber is composed of basalt fibers with a length of 1 mm and a diameter of 1 μm, basalt fibers with a length of 15 mm and a diameter of 10 μm, and basalt fibers with a length of 50 mm and a diameter of 9 μm in a weight ratio of 10:4:1. The polyester fiber is 30mm long and has a fineness of 1.5D. The aramid fiber has a length of 10mm and a fineness of 1.5D. Preparation of hemp fiber felt layer: Hemp fiber and nylon fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out, cured, and hemp fiber felt layer is obtained. The length of the hemp fiber is 20mm, and the metric count is 10Nm. Nylon fiber 10mm, fineness 1.5D; Preparation of composite speaker diaphragm: The wuyan surface felt layer, the hemp fiber felt layer and the wuyan surface felt layer are stacked in sequence, placed in a molding equipment, and pressed to form a composite speaker diaphragm for car audio.
[0040] The needle-punching process in the preparation of the felt layer on the surface of Wuyan is as follows: The double-sided needle puncture is performed alternately on the front and back sides. First, pre-needling is performed with a needle density of 150 needles / cm², a needle depth of 8mm, and a feed speed of 2m / min. Then, the main needle puncture is performed with a needle density of 400 needles / cm², a needle depth of 10mm, and a feed speed of 4m / min.
[0041] The needle-punching process in the preparation of hemp fiber felt layers is as follows: The double-sided needle puncture is performed alternately on the front and back sides. First, pre-needling is performed with a needle density of 250 needles / cm², a needle depth of 6mm, and a feed speed of 1m / min. Then, the main needle puncture is performed with a needle density of 700 needles / cm², a needle depth of 12mm, and a feed speed of 3m / min.
[0042] The phenolic resin adhesive is composed of phenolic resin (203 phenolic resin), a flexibility agent (polyethylene glycol 800), a penetrant (fatty alcohol polyoxyethylene ether), and a solvent (ethanol) in a weight ratio of 70:4:0.1:70.
[0043] The thickness ratio of the first basalt surface felt layer, the hemp fiber felt layer, and the second basalt surface felt layer is 0.5:5:0.5.
[0044] The difference between Examples 2-3 and Example 1 lies in the types, amounts, and parameters of raw materials used in preparing the composite speaker diaphragm for automotive audio systems. Specific differences are shown in Table 1. Table 1. Types, amounts, and parameters of raw materials used in the preparation of composite speaker diaphragms for automotive audio systems.
[0045]
[0046] Example 4 A composite speaker diaphragm for car audio is described in this embodiment, which differs from Embodiment 1 in that the weight ratio of the three basalt fibers is 1:1:1.
[0047] Example 5 A composite speaker diaphragm for car audio is disclosed in this embodiment, which differs from Embodiment 1 in that basalt fibers are immersed in a silane coupling agent ethanol solution (3-aminopropyltriethoxysilane ethanol solution, weight concentration of 2%) for 20 minutes, then removed and dried to obtain pretreated basalt fibers.
[0048] Example 6 A composite speaker diaphragm for car audio is disclosed in this embodiment, which differs from Embodiment 1 in that basalt fibers are immersed in a silane coupling agent ethanol solution (3-aminopropyltriethoxysilane ethanol solution, weight concentration of 1%) for 30 minutes, then removed and dried to obtain pretreated basalt fibers.
[0049] Example 7 A composite speaker diaphragm for car audio is described in this embodiment, which differs from Embodiment 1 in that the length of the hemp fiber is 10 mm and the metric count is 1000 Nm.
[0050] Example 8 A composite speaker diaphragm for car audio is disclosed in this embodiment, which differs from Embodiment 1 in that the phenolic resin adhesive is composed of phenolic resin, penetrant, and solvent in a weight ratio of 70:0.1:70. Preparation Example
[0051] Comparative Example 1 A composite speaker diaphragm for car audio is described. The difference between this comparative example and Example 1 is that the basalt fiber is a basalt fiber with a length of 1 mm and a diameter of 1 μm.
[0052] Comparative Example 2 A composite speaker diaphragm for car audio is disclosed. The difference between this comparative example and Example 1 is that the basalt fiber is basalt fiber with a length of 50 mm and a diameter of 9 μm.
[0053] Comparative Example 3 A composite speaker diaphragm for car audio is disclosed. The difference between this comparative example and Example 1 is that the basalt fiber is composed of basalt fibers with a length of 1 mm and a diameter of 1 μm and basalt fibers with a length of 50 mm and a diameter of 9 μm in a weight ratio of 10:1.
[0054] Comparative Example 4 A composite speaker diaphragm for car audio is described. The difference between this comparative example and Example 1 is that no polyester fiber is added during the preparation of the felt layer on the surface of the diaphragm.
[0055] Comparative Example 5 A composite speaker diaphragm for car audio is disclosed. The difference between this comparative example and Example 1 is that polypropylene fibers are used instead of polyester fibers in the preparation of the felt layer on the surface of the diaphragm.
[0056] The polypropylene fiber is 30mm long and has a fineness of 1.5D.
[0057] Comparative Example 6 A composite speaker diaphragm for car audio is described. The difference between this comparative example and Example 1 is that no aramid fiber is added during the preparation of the felt layer on the surface of the diaphragm.
[0058] Comparative Example 7 A composite speaker diaphragm for car audio is disclosed. The difference between this comparative example and Example 1 is that nylon fibers are replaced with polyester fibers in the preparation of the hemp fiber felt layer.
[0059] Detection methods / test methods Frequency response: According to GB / T 12060.5, in a standard anechoic chamber, use a B&K 4192 measuring microphone to measure the frequency response of 20Hz-20kHz at a distance of 1m from the diaphragm. If the sound pressure fluctuation in the 200Hz-500Hz frequency band is ≤±6dB and there are no obvious peaks and valleys, it is considered qualified.
[0060] Stiffness test: Refer to GB / T 1449-2005 "Test method for bending properties of fiber reinforced plastics" to conduct a three-point bending test and determine the bending modulus.
[0061] Interlaminar shear strength test: The test was conducted in accordance with GB / T 1450.2-2008 "Fiber-reinforced plastics - Stamping shear strength test method".
[0062] Temperature-humidity cyclic aging test, accelerated aging is performed according to the following cycle: High temperature and high humidity: 70℃ / 90%RH, maintain for 4 hours Low temperature and low humidity: -30℃ / 30%RH, maintain for 4 hours The conversion time was 30 minutes, the number of cycles was -500, and then the frequency response and interlaminar shear strength were tested. The experimental data are shown in Table 2: Table 2 Experimental data of Examples 1-8 and Comparative Examples 1-7
[0063] The experimental data above show that the composite speaker diaphragm for car audio produced by the process and formula of this application can still maintain a frequency response of ≤6dB (qualified) and a high interlayer shear strength retention rate after 500 temperature and humidity cycles in the harsh car cabin environment of -30℃ to 70℃. This effectively solves the technical problem that the interlayer interface of existing composite diaphragms lacks effective resistance to temperature-humidity cyclic loads.
[0064] Comparing Example 1 and Comparative Examples 1-2, it can be seen that the combined use of three different lengths and diameters of basalt fibers significantly improves the cohesive strength of the felt layer on the basalt surface and the interlayer mechanical interlocking effect. Simultaneously, the micro-stress generated by fibers of different scales under temperature and humidity changes can be gradually dispersed through the gradient structure, avoiding interface cracking caused by concentrated stress on fibers of a single scale.
[0065] Compared with Examples 1 and Comparative Examples 4-6, this application demonstrates that by preparing a basalt surface felt layer using basalt fiber, polyester fiber, and aramid fiber, it is beneficial to improve its stiffness and high interfacial strength.
[0066] Compared with Example 1 and Comparative Example 7, the synergistic use of nylon fiber and hemp fiber is beneficial for rapidly dissipating ringing energy and shortening the ringing decay time. It can also effectively buffer interlayer stress under temperature and humidity cycling and suppress interface debonding, thus simultaneously satisfying high internal damping and long-term interface durability.
[0067] A comparison of Examples 1 and Examples 4-8 demonstrates that optimizing the proportions and process parameters of each component in this application can further improve flexural modulus, interlaminar shear strength, or frequency response performance, thereby achieving a balance between high-fidelity acoustic performance and long-term environmental stability.
[0068] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A composite speaker diaphragm for car audio systems, characterized in that, The composite speaker diaphragm for car audio systems comprises, in sequence, a first basalt surface felt layer, a hemp fiber felt layer, and a second basalt surface felt layer. Both the first and second basalt surface felt layers are prepared from the following raw materials in parts by weight: 60-80 parts of basalt fiber 5-10 parts polyester fiber 3-5 parts of aramid fiber Appropriate amount of phenolic resin glue The basalt fiber is obtained by mixing three types of basalt fibers of different lengths and diameters.
2. The composite speaker diaphragm for automotive audio systems according to claim 1, characterized in that: The basalt fiber is composed of basalt fibers with a length of 1-10 mm and a diameter of 1-5 μm, basalt fibers with a length of 15-40 mm and a diameter of 10-30 μm, and basalt fibers with a length of 50-80 mm and a diameter of 9-15 μm in a weight ratio of 10:4-7:1-3.
3. The composite speaker diaphragm for automotive audio systems according to claim 2, characterized in that: The polyester fibers are 30-50 mm in length and 1.5-3D in fineness. The aramid fibers are 10-20 mm in length and 1.5-2D in fineness.
4. The composite speaker diaphragm for automotive audio systems according to claim 1, characterized in that, The basalt fibers are pretreated using the following method: Basalt fibers are immersed in a silane coupling agent ethanol solution for 20-30 minutes, then removed and dried to obtain pretreated basalt fibers.
5. The composite speaker diaphragm for automotive audio systems according to claim 1, characterized in that, The hemp fiber felt layer is prepared from the following raw materials in parts by weight: 80-90 parts of hemp fiber 4-6 parts nylon fiber Appropriate amount of phenolic resin adhesive.
6. The composite speaker diaphragm for automotive audio systems according to claim 5, characterized in that: The length of the hemp fiber is 20-50mm, and the metric count is 10-20Nm. The nylon fibers are 10-25mm in diameter and have a fineness of 1.5-6D.
7. The composite speaker diaphragm for automotive audio systems according to claim 6, characterized in that: The phenolic resin adhesive is composed of phenolic resin, a flexible agent, a penetrant, and a solvent in a weight ratio of 70-80:4-8:0.1-0.3:70-80.
8. The composite speaker diaphragm for automotive audio systems according to claim 1, characterized in that: The thickness ratio of the first basalt surface felt layer, the hemp fiber felt layer, and the second basalt surface felt layer is 0.5-1:5:0.5-1.
9. A method for preparing a composite speaker diaphragm for automotive audio systems as described in any one of claims 1-8, characterized in that, The preparation steps include the following: Preparation of basalt surface felt layer: Basalt fiber, polyester fiber and aramid fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out and cured to obtain basalt surface felt layer. Preparation of hemp fiber felt layer: Hemp fiber and nylon fiber are opened separately, then mixed, dry carded into a web, needle punched, then impregnated in an appropriate amount of phenolic resin, taken out, cured, and hemp fiber felt layer is obtained. Preparation of composite speaker diaphragm: The wuyan surface felt layer, the hemp fiber felt layer and the wuyan surface felt layer are stacked in sequence, placed in a molding equipment, and pressed to form a composite speaker diaphragm for car audio.
10. The method for preparing a composite speaker diaphragm for automotive audio systems according to claim 9, characterized in that: The temperature of the upper and lower molds in the molding equipment is 210-230℃, the molding pressure is 0.2-0.4MPa, the hot mold molding time is 20-30S, and the cold mold setting time is 5-10S.
